2015
DOI: 10.17065/huniibf.103641
|View full text |Cite
|
Sign up to set email alerts
|

‘Çevre’ Ülkelerinde Finansal Gelişme ile Büyüme Arasındaki İlişki: Panel Veri Analizi

Abstract: The Relationship between Financial Development and Growth in Peripheral Countries: A Panel Data AnalysisThe relation between 'financial liberalisation' policies and 'economic growth' have started at the beginning of 2008 in USA and after a period of time, it has been the focal point one more time with the financial crisis that influenced the whole liberal capitalist system. By according with the tendency, the relation between the financial development degree and the economic growth for a group of neighboring c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…Studies investigating the relationship between financial development and growth have used panel data analysis methods as well as time series analysis. Among these studies; Goldsmith (1969), Levine (1997), Levine et al (2000), Thangavelu and James (2004), Nazlıoğlu, Yalama et al (2009), Wu et al (2010), Aydın et al (2014), Hayaloğlu (2015), İnançlı et al (2016), Eren and Ünal (2019), Alasgarli and Sekmen (2021) found a positive relationship between the two variables, while Naceur and Ghazouani (2007), Altıntaş and Ayrıçay (2010), Williams (2016), Aydın et al (2013), Li and Ingham (2020) obtained empirical evidence that the relationship is negative.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies investigating the relationship between financial development and growth have used panel data analysis methods as well as time series analysis. Among these studies; Goldsmith (1969), Levine (1997), Levine et al (2000), Thangavelu and James (2004), Nazlıoğlu, Yalama et al (2009), Wu et al (2010), Aydın et al (2014), Hayaloğlu (2015), İnançlı et al (2016), Eren and Ünal (2019), Alasgarli and Sekmen (2021) found a positive relationship between the two variables, while Naceur and Ghazouani (2007), Altıntaş and Ayrıçay (2010), Williams (2016), Aydın et al (2013), Li and Ingham (2020) obtained empirical evidence that the relationship is negative.…”
Section: Literature Reviewmentioning
confidence: 99%